Factors of community innovation in the life of settlements - Slezák-Bartos, Zsuzsanna (Acta Cultura et Paedagogicae, 2026)
Nowadays, residents have ever higher expectations of their local communities. To do this, they need to be aware of the values and potential of their place of residence. First and foremost, local people need to be made aware of the values of the city, as their positive perception of the city's liveability has a multiplier effect on the perception of the city. Settlements are central sites of social interaction and relationships, influencing people's quality of life and well-being. By examining the context of settlement philosophy, cities can be designed and developed with a focus on community life, and also play an important role in promoting social justice and inclusive settlement development. The uniqueness and diversity of gastronomic culture reflects the principles and values of the philosophy of settlement. In a municipality where sustainability and an emphasis on local production are central to community life, businesses and families follow gastronomic traditions, preferring ingredients from local producers and preparing food according to local characteristics. At the same time, gastronomic diversity enriches and diversifies the philosophy of a settlement, and the diversity of the gastronomic offer of a given settlement enables its inhabitants to learn about the food and eating habits of other cultures, thus further developing social diversity and cohesion within a community.